COMPROMISE, UNDUE INFLUENCE AND ECONOMIC DURESS Gerolomou Constructions (Pty) Ltd v Van Wyk 2011 (4) SA 500 (GNP) - CJ Pretorius; R Ismail (Obiter, 2021)
The matter of Gerolomou Constructions (Pty) Ltd v Van Wyk (2011 (4) SA 500 (GNP)) alludes to two rather problematic aspects of the law of contract: on the one hand it demonstrates that practically speaking the question of what constitutes an enforceable agreement of compromise is still no easy matter, and despite the sound judgment delivered recently by the Supreme Court of Appeal in Be Bop A Lula Manufacturing & Printing CC v Kingtex Marketing (Pty) Ltd (2008 (3) SA 327 (SCA)), it seems that the judiciary’s interpretation as to when an offer of compromise exists remains difficult to predict. On the other hand the Gerolomou decision deals with improperly obtained consensus by way of undue influence, whereas the facts actually fit more comfortably into the niche of so-called economic duress, a form of procedural impropriety that has yet to be recognized as an independent ground for setting aside a contract in our law. This case note examines these issues against the backdrop of the manner in which the case was pleaded.